Increased Synapse Formation Obtained by T Cell Epitopes Containing a CxxC Motif in Flanking Residues Convert CD4+ T Cells into Cytolytic Effectors - Carlier, Vincent A. (Public Library of Science, 2012)
The nature of MHC class II-binding epitopes not only determines the specificity of T cell responses, but may also alter effector cell functions. Cytolytic CD4+ T cells have been observed primarily in anti-viral responses, but very little is known about the conditions under which they can be elicited. Their potential as regulators of immune responses, however, deserves investigations. We describe here that inclusion of a thiol-disulfide oxidoreductase motif within flanking residues of class II-restricted epitopes results, both in vitro and in vivo, in elicitation of antigen-specific cytolytic CD4+ T cells through increased synapse formation. We show that both naïve and polarized CD4+ T cells, including Th17 cells, can be converted by cognate recognition of such modified epitopes. Cytolytic CD4+ T cells induce apoptosis on APCs by Fas-FasL interaction. These findings potentially open the way towards a novel form of antigen-specific immunosuppression.